O05 Evaluation of the implementation of an express 'test-and-go' hiv/sti testing service for men who have sex with men in sexual health centre. (8th June 2017) - Chow, Eric; Fortune, Ria; Dobinson, Sheranne; Read, Tim; Chen, Marcus; Bradshaw, Catriona; Fehler, Glenda; Fairley, Christopher
Abstract : Introduction: Men who have sex with men (MSM) who are asymptomatic and do not require treatment are eligible to use the new express HIV/STI testing service called 'Test-And-GO' (TAG) or the general clinic service for an asymptomatic screen. We aimed to evaluation the utilisation of the TAG service. Methods: MSM attending the clinic for a TAG service or a general clinic service between 5 August 2015 and 1 June 2016 were analysed. A general estimating equation regression model was constructed to examine the association between the use of TAG service and demographic characteristics, sexual behaviours, and HIV/STI diagnoses. Results: Of the 4, 212 consultations, 750 (17.8%) were TAG consultations and 3, 462 (82.2%) were routine consultations for asymptomatic MSM at the general clinic. MSM were more likely to use the TAG service if they were aged >30 years (OR=1.32 [95% CI 1.10–1.58]), were born in Australia (OR=1.40 [95% CI 1.16–1.70]), and had ≤4 male partners in the last 12 months (OR=1.30 [95% CI 1.12–1.52]) but there was no significant difference between condom use in the last 12 months. MSM who used the TAG service had less syphilis but there were no differences in detection of gonorrhoea, chlamydia and HIV diagnoses between the two services. Discussion: Demographic and some behavioural characteristics differed between the two services but other than syphilis there was no difference in STIs. The TAG service required less clinician time and hence created additional clinical capacity at the general clinic to see patients at higher risk.